Nutrients, antinutrients and detoxification of crambe meal for use in animal nutrition - Pretto, Alexandra; Silva, Leila Picolli da; Giacomini, Sandro José; Martinelli, Suziane Ghedini; Prati, Ricardo Lourega; Nunes, Lucas Mesquita da Costa (Semina: Ciências Agrárias, 2014)
Associated with biofuels production from plant sources, there is generation of several byproducts suitable to use in animal nutrition, which requires careful study for wide and safe applicability. Crambe meal is a byproduct still poorly understood and studies are needed to better assess their nutritional potential. In this context, the present study was carried out with the aim of measuring the chemical groups of interest (nutrients and antinutrients) and in vitro protein digestibility of crambe meal in nature and reduced antinutrients forms. For removal antinutrients were applied acidic (adding concentrated sulfuric acid to water until pH 1.0) and alcoholic (commercial ethanol 92.8º) solutions on in nature meal. The results showed that chemical treatment increased the fiber and ash content and reduced the crude protein, amino acids, fat, calcium and phosphorus content as well as phenolic compounds, tannins (total, condensed and hydrolysable) and phytic acid. Although the chemical treatment has changed the balance of the constituents of most of nutritional interest, its effect was not observed in in vitro protein digestibility. The nutritional and antinutritional character obtained for this meal can collaborate in indicative of an alternative protein source for animal nutrition.